2015
DOI: 10.5530/jyp.2015.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Medication Reconciliation and Medication Error Prevention in an Emergency Department of a Tertiary Care Hospital

Abstract: Objective: The study was conducted to assess the effectiveness of the medication reconciliation and medication error prevention in an emergency department of a tertiary care hospital. Materials and Methods: Patients of either sex, aged above 18 years admitted for more than 24 hours irrespective of their medical diagnosis and for whom medication reconciliation was done were included. Patients' home medication charts were compared with their current admission medication charts to check the number of home medicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
(15 reference statements)
2
16
1
Order By: Relevance
“…In a total of 287 prescription errors, strength of the drug was not mentioned in 194 drugs (67.6%). This result is similar to the study conducted by Poornima et al, a total of 131 errors, strength of the drug was mentioned in 42 drugs (32.06%) [10].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a total of 287 prescription errors, strength of the drug was not mentioned in 194 drugs (67.6%). This result is similar to the study conducted by Poornima et al, a total of 131 errors, strength of the drug was mentioned in 42 drugs (32.06%) [10].…”
Section: Discussionsupporting
confidence: 91%
“…Their study shows that, in 30 cases 26 medication errors were identified. In which 44 (33.58%) DDIs were obtained, and thus it becomes the leading error in their study [10].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Up to the researchers’ knowledge, this is the first study to be conducted in Jordan to evaluate the value of this effective pharmaceutical care service. Results of this study add to the literature in this area, highlighting the important role of the pharmacist in detecting medication discrepancies and in preventing medical errors in the hospital setting …”
Section: Discussionmentioning
confidence: 66%
“…Medication errors (MEs) may occur at any stage of medication use process, 1 either in hospital or after the discharge which can lead to preventable adverse drug events. 2 MEs during discharge are responsible for onethird of the adverse drug events.…”
Section: Introductionmentioning
confidence: 99%